(untitled) (Docentes 2.0 Journal, 2026)
In contemporary Colombian education, students’ English proficiency in public schools has become a key indicator of quality, especially given its connection to access to higher education and employment. The objective of this essay was to argue for and theoretically substantiate the need to integrate a focus on form with the intensive reading of authentic texts, moving beyond fragmented instruction based on isolated rules and decontextualized exercises. The essay employed a deductive method within the positivist paradigm, using a quantitative approach and an interpretive narrative-topical design. It centered on the conceptual analysis of the relationship between grammar and reading comprehension in the Colombian context. Based on a review of the theoretical background and educational policies on bilingualism, an argument was developed linking communicative competence with integrative teaching practices, maintaining that grammatical work is more effective when embedded in meaningful reading. The analysis reaffirmed that separating grammar and comprehension limits students’ linguistic development, whereas integrating them fosters deeper, more functional learning. Consequently, it is concluded that a teaching approach based on this integration is a coherent and necessary way to strengthen English language teaching in secondary education.